An integrated alarm with clamp system to mitigate vascular access bleeding in hemodialysis: a prospective cohort mixed methods study - Ryan J. Chan; Margaret McGrath-Chong; Christopher T. M. Chan (BMC Nephrology)
Abstract Establishing and maintaining a functional vascular access is essential for patients with end-stage kidney disease on home hemodialysis. Due to patient safety concerns about vascular access complications, particularly needle dislodgement causing bleeding, various technologies have emerged. The purpose of this study was to investigate whether a novel device (developed by Redsense Medical AB) consisting of a sensor placed at the venous puncture site and linked to a base unit with wireless connection to a clamp on the venous line is acceptable from a patient perspective and feasible for implementation in a home hemodialysis program. This was a prospective cohort study of patients undergoing home hemodialysis at the University Health Network in Toronto, Ontario, Canada. We conducted a mixed methods study with a convergent parallel design, collecting both quantitative and qualitative data through two patient questionnaires whereby patients rated their experience with the Redsense system after their first 1–3 treatments and after their last treatment with the system. Thematic analysis was performed with use of open coding and axial coding. Quantitative data was presented as a heat map depicting participants’ scoring of the Redsense system. Differences between the two questionnaires were assessed by Wilcoxon matched-pairs signed rank tests, and the response to select questions were depicted graphically. 21 patients consented to participate in this study, completing a total of 218 dialysis treatments with the Redsense system. Over these treatments, the system was shown to be safe and feasible for patients to use independently at home. The alarm had a relatively elevated false positive rate for both alarm triggering and clamp closure, with this sentiment well described in the qualitative data, as the nuisance of false alarms was a frequent concern described in the post-treatment questionnaire. Patients had other negative comments related to the practicality of the alarm system, the additional burden created, and concern about technical issues relating to wireless technology. Taken together, the data from this study suggest that most patients performing home hemodialysis independently feel that the potential benefits of the Redsense alarm system are outweighed by the additional burden and other negatives associated with the system.